2021
DOI: 10.31098/bmss.v1i1.254
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Consumers’ Purchase Behaviour towards Green Packaged Products

Abstract: The disposal of plastic packaging has caused the amount of waste generation, which have a negative impact on the environment. Green packaging, which is more eco-friendly packaging, is harmless to human health and biodegradable. Many businesses have turned to the movement of going green by providing green products and services. Hence, the objective of this study is to investigate the factors that influence the purchase behaviour of consumers towards green packaged products. A total of 200 respondents was recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…This finding jibes with the study of Ling et al (2022), who also found that consumers who are supporters of environmental sustainability tend to purchase environmentally friendly products. As further supported by Shifali and Amarjit (2022), individuals who are working professionals and have higher educational qualifications have significantly higher levels of awareness of green or environmental consumerism compared with other sectors of society.…”
Section: Individual Well-beingsupporting
confidence: 83%
“…This finding jibes with the study of Ling et al (2022), who also found that consumers who are supporters of environmental sustainability tend to purchase environmentally friendly products. As further supported by Shifali and Amarjit (2022), individuals who are working professionals and have higher educational qualifications have significantly higher levels of awareness of green or environmental consumerism compared with other sectors of society.…”
Section: Individual Well-beingsupporting
confidence: 83%